Android-based Information System for Domestic Violence Complaints at P2TP2A Institution in Boalemo Regency - Syaifuddin Lily; Ona Maliki; Muliati Badaruddin (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The Integrated Service Center for Women and Children Empowerment (P2TP2A) in Boalemo Regency is an institution that provides services to the community in cases of Domestic Violence (KDRT). The issue that arises is the lack of public knowledge about KDRT and its handling. It is important to continuously educate the community about the negative consequences of domestic violence and the importance of supporting victims and preventing such violence. With increased awareness and community participation, it is hoped that domestic violence can be minimized and eliminated, creating a safe and harmonious environment for all family members. Cases of KDRT continue to occur without being realized by the community and are rarely reported to the Center for Domestic Violence Services (PLKB) due to a lack of information on how to report KDRT cases to the PLKB. Most people feel that the complaint service is limited to reporting without any follow-up process. The research objective is to design an information system that provides information about KDRT as a means of socialization to the community and assists the community in reporting KDRT cases easily and flexibly through Android smartphones. The system analysis method used in this research is the Research and Development (R&D) method, which aims to produce a specific product and test its effectiveness. This application is developed using Java and PHP programming languages, with MySQL as the database for data storage. The system utilizes web service techniques to retrieve data from the server. The result of this research is an application of an information system that facilitates the presentation of information about KDRT through Android smartphones, equipped with online reporting features, and can map the location of the reporter to facilitate follow-up actions by the PLKB. The calculation results show that the Cyclomatic Complexity (CC) = 2 and V (G) = 2, indicating that the system is effective and efficient. The system implementation can be done on Android version 10.0 (Q), version 9.0 (Pie), and version 8.0 (Oreo).